PORTRAYAL OF CIVIL AND MILITARY LEADERSHIP OF PAKISTAN IN THE BRITISH PRINT MEDIA: A TEXTUAL ANALYSIS OF THE GUARDIAN AND TELEGRAPH - Ali, Shahzad (PEOPLE: International Journal of Social Sciences, 2017)
The study aimed to explore representation of civil and military leadership of Pakistan in the two mainstream newspapers of the UK i.e. the Guardian and the Telegraph through the lenses of qualitative textual analysis. It analyzed 25 leading articles and byline stories as the sample was selected through purposive sampling technique. The study was theoretically linked Shoemaker and Rees’s theory of influences on media contents and propaganda model of Herman and Chomsky. Overall mix representation of political leadership was explored with binary frames of popular charismatic leaders, puppets of military establishment, assertive, symbol of corruption and bad governance, champion of human rights, orthodox and fundamentalist, pro west, pro militant and ally of the US etc. The selected newspapers painted positive image of Farooq Ahmad Khan Laghari then President of Pakistan and Salman Tasser, governor of the province Punjab and paid tribute to him for raising his voice against the blasphemy law. While on the other hand the military leadership was framed with negative attributes as anti-democrat, disobedient to civilian leadership and as state within the state. Among the military leadership, three- fourth coverage of General Ishfaq Pervez Kiyani was found neutral to military leadership. While the Chief of Army Staff, General Raheel Sharif was portrayed in favorable manners.